Tradition and transformation: The role of Pashtunwali in shaping women's political identities - Shah, Sulman (Вестник Томского государственного университета. История)
This research investigates the impact of Pashtunwali on the women of Pashtun's political behavior, concentrating on how it restricts their political involvement. Via feminist geographical framework, the research engages in thematic textual analysis of historical texts and case studies, including the Afghan activist Malala Joya, the study high-lights how legal reforms, education and social movements resist the gender's values of Pashtunwali. It concludes that while Pashtunwali implements values of patriarchy, reinterpretation of its values can assist women in their political rights and fostering change.